2019
DOI: 10.1002/jbio.201900102
|View full text |Cite
|
Sign up to set email alerts
|

The inner clock—Blue light sets the human rhythm

Abstract: Visible light synchronizes the human biological clock in the suprachiasmatic nuclei of the hypothalamus to the solar 24‐hour cycle. Short wavelengths, perceived as blue color, are the strongest synchronizing agent for the circadian system that keeps most biological and psychological rhythms internally synchronized. Circadian rhythm is important for optimum function of organisms and circadian sleep–wake disruptions or chronic misalignment often may lead to psychiatric and neurodegenerative illness. The benefici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
136
1
26

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(165 citation statements)
references
References 118 publications
2
136
1
26
Order By: Relevance
“…Furthermore, physical inactivity can be associated with disorders such as sleep apnea, which is associated with lower sleep quality [ 30 ]. Similarly, higher sedentary behavior, especially screen time can be associated with higher exposure to blue light, which can affect mechanisms related to melatonin release, which is detrimental to sleep quality [ 31 ]. In this sense, poorer sleep quality due to the incidence of unhealthy movement behaviors could explain part of the association of the incidence of unhealthy movement behavior and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, physical inactivity can be associated with disorders such as sleep apnea, which is associated with lower sleep quality [ 30 ]. Similarly, higher sedentary behavior, especially screen time can be associated with higher exposure to blue light, which can affect mechanisms related to melatonin release, which is detrimental to sleep quality [ 31 ]. In this sense, poorer sleep quality due to the incidence of unhealthy movement behaviors could explain part of the association of the incidence of unhealthy movement behavior and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that viewing light with significant energy levels in the blue spectrum near the time when we would normally expect to sleep can negatively impact our circadian rhythms by activating a specific type of retinal cells—intrinsically photosensitive retinal ganglion cells (ipRGCs)—that suppress the sleep hormone melatonin. Studies have found that all light has this suppressive effect to some degree, but blue light's wavelength suppresses melatonin to a far greater extent than warmer colors on the visible spectrum 1 …”
Section: Understanding the Connection Between Blue Light And Healthmentioning
confidence: 99%
“…However, light exposure between morning and evening does not affect the phase of the biological clock [17]. In addition, nighttime light exposure suppresses the secretion of melatonin, a sleep-promoting hormone, from the pineal gland [18][19][20]. This can interfere with sleep onset [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, ST just before bedtime can be problematic. Among the visible light wavelengths, short wavelengths perceived as the color blue can strongly affect the phase delay of the circadian rhythm, along with suppressing melatonin [18][19][20]. Most digital devices emit blue light.…”
Section: Introductionmentioning
confidence: 99%